Definition and Effectiveness of Competences in Cultural Management System: Case Study of the Activities of the Heads of Lithuanian Cultural Centers - Survutaitė, Dalia; Rutkienė, Aušra; Gedvilienė, Genutė (Acta Paedagogica Vilnensia, 2025)
Competence-based education and professional development have been topics of discussion among social science researchers in the field of educational science since the late 20th century. This article presents the definition of competence in the context of culture. It examines the identity of cultural centre leaders through the lens of social and pragmatic constructivism theories. Two qualitative studies analysed the performance of cultural centre leaders. The links between the identified domains and competences were evaluated, leading to the identification of characteristic competencies. A quantitative survey of cultural centre leaders established their typical activities. The study confirms that the activities of cultural centre heads not only preserve the cultural heritage, mobilise the community, and maintain relationships with society, but also create new meanings of culture. It was determined that the competences of the managers of cultural centres address not only the (re)production of culture, but also the making of sense through its development.
Keywords: areas of activity; heads; competences; culture; cultural centre